Intensified rotary drum bioreactor for cellulase production from agro-industrial residues by solid-state cultivation - Grajales, Lina María (2025)
Cellulolytic enzymes are vital for converting cellulosic residues into biofuels, yet large-scale production through solid-state cultivation (SSC) remains challenging due to the lack of suitable bioreactors. This study addresses this issue by developing a rotary drum bioreactor to produce cellulases from the thermophilic fungus Myceliophthora thermophila I-1D3b, using sugarcane bagasse and wheat bran as substrates. The bioreactor integrates upstream, fermentation, and downstream processes, streamlining production and enhancing efficiency. The study explored enzymatic activity (EA) at varying substrate loadings and drum rotation conditions. Although statistically similar, at 50 % loading, drum rotation slightly improved EA (49.12 U/mL ± 6.56 U/mL) compared to static conditions (47.78 U/mL ± 8.25 U/mL). Conversely, at 40 % loading, rotation reduced EA significantly (23.57 U/mL ± 3.17 U/mL) compared to static conditions (46.91 U/mL ± 8.17 U/mL). At 60 % loading, EA was similar under both static and rotated conditions. The design effectively supports fermentation, facilitates enzymatic extract recovery, and minimizes temperature and moisture gradients. These results demonstrate the rotary drum bioreactor's potential for scaling up cellulase production, offering a promising solution for industrial SSC processes.